A Comprehensive Evaluation and Mitigation Approaches for Traffic-Related Noise in the Sungai Long Region, Malaysia - Lee Hang Tan; Ming Han Lim; Yee Ling Lee; Hooi Ling Khoo (Transactions on Transport Sciences, 2024)
The fast development of technology and transportation systems has resulted in a disturbing level of noise pollution over time that requires research and regulatory. Most existing research is deemed ineffective as it primarily focuses on conducting assessments of traffic noise without providing a structured framework for noise mitigation. This study focused on three main stages to monitor road traffic noise in Sungai Long area: (1) examination of traffic features, (2) derivation of noise indices, and (3) evaluation of the influence of traffic noise. Total of four roads were selected with four stations on each road in Bandar Sungai Long to assess the traffic noise impact. The sound level metre (SLM) was used to calculate the noise indices for each road. Besides, peak-hour sessions and off-peak sessions of traffic flow were measured in field measurement to compare the differences in noise conditions. Additionally, based on the measured noise indices, traffic noise index (TNI), noise pollution level (LNP), and expected community response were calculated to reveal the impact of traffic noise. Overall, this study's findings demonstrated that residential areas experiencing traffic noise disturbance, particularly on roads, namely Jalan Bp Satu and Jalan Persiaran SL 7, had exceeded the Malaysian environmental standard. In addition, two optimized methods are proposed which are prohibiting heavy vehicles and a simple noise barrier was designed on Jalan Bp Satu and Jalan Persiaran SL 7. The expected noise level between these two methods had been compared in the discussion part. In summary, prohibiting heavy vehicles on the road is more suitable if the aim is to save cost. However, if reducing traffic noise is a priority and a long-term solution is needed, constructing noise barrier may be a more effective solution.